2017
DOI: 10.21666/muefd.303856
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Dönemdeki Çocuklara Eğitsel Oyunlar Yoluyla Kazandırılan Değerler

Abstract: ÖzetBu araştırmanın amacı, okul öncesi dönemdeki çocuklara eğitsel oyunlar oynatılarak onların ne gibi değerler kazandığını ortaya çıkarmaktır. Araştırmada nitel araştırma yöntemlerinden eylem araştırması deseni kullanılmıştır. Araştırma, 2015-2016 öğretim yılında, Isparta iline bağlı Eğirdir ilçe merkezindeki devlet okulunda öğrenim gören okul öncesi öğrencilerinden 23 öğrenciye her gün bir oyun olmak üzere toplamda 10 adet eğitsel oyunun oynatılması yoluyla gerçekleştirilmiştir. Araştırmada, örneklem belirle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 3 publications
1
7
0
7
Order By: Relevance
“…Educational play helps children not only develop various skills but also build social relationships that would contribute to the development of values. Peer socialization provides children with an opportunity to learn the values of respect, kindness, happiness, helpfulness, tolerance, responsibility, patience, belonging, sensitivity, courage, justice, and virtuous deeds without any coercion and pressure (Gündüz, Aktepe, Uzunoğlu and Gündüz, 2017). Participants' third choice was story reading, which is also consistent with the studies (Ural, 2013: 47-48) which assert that the story reading method contributes to moral education and helps children learn social and moral values.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 63%
See 1 more Smart Citation
“…Educational play helps children not only develop various skills but also build social relationships that would contribute to the development of values. Peer socialization provides children with an opportunity to learn the values of respect, kindness, happiness, helpfulness, tolerance, responsibility, patience, belonging, sensitivity, courage, justice, and virtuous deeds without any coercion and pressure (Gündüz, Aktepe, Uzunoğlu and Gündüz, 2017). Participants' third choice was story reading, which is also consistent with the studies (Ural, 2013: 47-48) which assert that the story reading method contributes to moral education and helps children learn social and moral values.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 63%
“…Eğitsel oyun; çocuğu birçok yönden geliştirdiği gibi aynı zamanda sosyal ilişkiler kurulmasına yardım ederek çocukta değer kavramının oluşmasına katkı sağlamaktadır. Akranlarıyla sosyalleşme şansı bulan çocuklar böylece saygı, nezaket, mutluluk, yardımseverlik, hoşgörü, sorumluluk, sabır, ait olma, duyarlılık, cesaret, adalet ve iyilik gibi değerleri hiçbir zorlama ve baskı olmadan kendi kurdukları ilişkiler yoluyla kazanmış olur (Gündüz, Aktepe, Uzunoğlu ve Gündüz, 2017). Ayrıca hikâye okuma tekniğinin yine verilecek ahlaki eğitime katkı sunacağı ve çocuklara sosyal değerler, etik değerler kazandıracağı öngörüsü yapılan araştırmalarla ile paralellik göstermektedir (Ural, 2013, s. 47-48).…”
Section: Sonuç Ve Tartışmaunclassified
“…One of them is a study conducted to determine the values that preschool children gain by playing educational games. As a result of this research, which was carried out by playing a total of 10 educational games, one game each day, with 23 preschool students; It has been observed that while educational games improve the social, emotional, physical, and mental aspects of the child, they also contribute to the formation of the concept of value in the child by helping him establish social relations (Gündüz et al, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Bundan dolayı öğretmenlerin doğru rol model olmaları ve çocuklara değerleri kazandırmaları önem arz etmektedir (Kozikoğlu, 2018). Bu amaçla drama, tiyatro (Gündüz, Aktepe, Uzunoğlu ve Gündüz, 2017), gözlem (Sapsağlam, 2017), soru-cevap, oyunlaştırma, rol yapma, gösteri, düz anlatım, örnek olay (Uzun ve Köse, 2017) gibi yöntem, teknik ya da etkinlikler kullanılarak çocuklara değerler kazandırılabilmektedir. Bu tür etkinlikler, çocuklar için soyut nitelikteki değerlerin somutlaştırılarak öğretilmesini sağlamaktadır (Kozikoğlu, 2018).…”
Section: Introductionunclassified
“…Okul öncesi dönemden itibaren kazandırılması gereken değerler, alanyazındaki birçok makalede (Aral ve Kadan, 2018;Cengiz ve Duran, 2017;Gündüz, Aktepe, Uzunoğlu ve Gündüz, 2017;Özdemir-Beceren ve Bilgen, 2019;Topaç, Bardak, Kirişci ve Mertoğlu, 2020;Yaka, Yalçın ve Denizli, 2014)…”
Section: Introductionunclassified